Using Technologies for Creative- Text Translation (Taylor & Francis, 2022)
creative texts; translation technologies; machine translation; computer-aided translation; translation practice
English
Keywords: Language: reference and general; Linguistics; creative texts; translation technologies; machine translation; computer-aided translation; translation practice